SHRINE SIGHTS OF OUR COUNTRY - Ismoilova Sevara; Daliquziyeva Dilafruz; Sayfullayeva Rukhshona (Scientific Impulse, 2024)
In this article, the measures aimed at preserving the history of our country and conveying historical landmarks to the younger generation are aimed at understanding our history.